Pharmacological effects of nanoencapsulation of human-based dosing of probucol on ratio of secondary to primary bile acids in gut, during induction and progression of type 1 diabetes - Mooranian, Armin; Zamani, Nassim; Takechi, Ryu; Al-Sallami, H.; Mikov, M.; Golocorbin-Kon, S.; Kovacevic, B.; Arfuso, Frank; Al-Salami, Hani (Taylor & Francis Inc., 2018)
INTRODUCTION: The ratio of secondary to primary bile acids changes during Type 1 Diabetes (T1D) development and these effects might be ameliorated by using cholesterol lowering drugs or hydrophilic bile acids. Probucol is a cholesterol-lowering drug, while ursodeoxycholic acid is a hydrophilic bile acid. This study investigated whether nanoencapsulated probucol with ursodeoxycholic acid altered bile acid ratios and the development of diabetes. METHODS: Balb/c mice were divided into three groups and gavaged daily with either free probucol, nanoencapsulated probucol or nanoencapsulated probucol with ursodeoxycholic acid for seven days. Alloxan was injected and once T1D was confirmed the mice continued to receive daily gavages until euthanasia. Blood, tissues, faeces and urine were collected for analysis of insulin and bile acids. RESULTS AND CONCLUSIONS: Nanoencapsulated probucol-ursodeoxycholic acid resulted in significant levels of insulin in the blood, lower levels of secondary bile acids in liver and lower levels of primary bile acids in brain, while ratio of secondary to primary bile acids remains similar among all groups, except in the faeces. Findings suggests that nanoencapsulated probucol-ursodeoxycholic acid may exert a protective effect on pancreatic ß-cells and reserve systemic insulin load via modulation of bile acid concentrations in the liver and brain.